Tradition of Abai in the poems by Magaz Razdanuly - Kadyl, Т. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article examines the literary evolution of Maghaz Razdanuly and the influence of Abai’s legacy on his work in both content and form. A prominent figure in Kazakh literature in China, Maghaz depicted the historical and social realities of Chinese society from the 1930s to the 1980s through his poetry. The study aims to reveal previously unexplored aspects of his creative output by analyzing poetry collections such as Asular Tolgaui, Uaqytqa Zhauap, Bosagha, and Erten. A comparative analysis with Abai’s works highlights Abai’s impact on Maghaz’s poetic philosophy and style. The research draws on insights from foreign scholars like Derek Johnston, Rémi Hess, and Nan Fan, as well as Kazakh thinkers such as Mukhtar Auezov and Garifolla Yesim, to deepen the theoretical framework. Particular attention is given to the philosophical richness of Maghaz’s prison poetry, shaped by personal hardship and historical turmoil. The study concludes that Maghaz Razdanuly continued and enriched Abai’s literary tradition, with his works offering both historical insight and contemporary relevance.